Synergism between food additives and heat to reduce postharvest sour rot of oranges - Palou, Lluís; Taberner, Verònica; Jerbi, Nihed; De-La-Fuente, Beatriz (2019)
Postharvest sour rot of citrus fruit, caused by Geotrichum citri-aurantii, is typically controlled with the application of specific fungicides such as propiconazole or guazatine (currently banned in the European Union). However, there is an increasing interest in the implementation of nonpolluting alternative control methods. In this research, 1 min dips in 3% aqueous solutions of the food additives sodium methyl paraben (SMP), sodium ethyl paraben (SEP), potassium sorbate (PS) and sodium benzoate (SB), all applied at 20 or 50°C, were evaluated with ‘Barnfield’ Navel oranges artificially inoculated with G. citri-aurantii about 24 h before treatment application. All treatments significantly reduced the incidence (percentage of infected fruit) and severity (lesion diameter) of the disease, and a strong synergy between food additives and heat was observed. After 6 days of incubation at 28°C, while disease incidence on control fruit (dipped in water at 20°C) was 80%, it was 13, 30, 43 and 13% on oranges dipped in SMP, SEP, PS and SB solutions at 20°C, and 0, 5, 10 and 0% on oranges dipped in solutions at 50°C, respectively. Nevertheless, heat increased the slight incidence of rind spots caused by some salt treatments. In a further assay, no significant differences in incidence and severity were found between rinsed (5 s spray with tap water at low pressure) and non-rinsed ‘Valencia Late’ oranges previously dipped in 3% SMP or SB solutions at 20°C.